A Late Form of Nucleophagy in Saccharomyces cerevisiae - Mijaljica, Dalibor; Prescott, Mark; Devenish, Rodney J. (PLOS ONE, 2012)
Autophagy encompasses several processes by which cytosol and organelles can be delivered to the vacuole/lysosome for breakdown and recycling. We sought to investigate autophagy of the nucleus (nucleophagy) in the yeast Saccharomyces cerevisiae by employing genetically encoded fluorescent reporters. The use of such a nuclear reporter, n-Rosella, proved the basis of robust assays based on either following its accumulation (by confocal microscopy), or degradation (by immunoblotting), within the vacuole. We observed the delivery of n-Rosella to the vacuole only after prolonged periods of nitrogen starvation. Dual labeling of cells with Nvj1p-EYFP, a nuclear membrane reporter of piecemeal micronucleophagy of the nucleus (PMN), and the nucleoplasm-targeted NAB35-DsRed.T3 allowed us to detect PMN soon after the commencement of nitrogen starvation whilst delivery to the vacuole of the nucleoplasm reporter was observed only after prolonged periods of nitrogen starvation. This later delivery of nuclear components to the vacuole has been designated LN (late nucleophagy). Only a very few cells showed simultaneous accumulation of both reporters (Nvj1p-EYFP and NAB35-DsRed.T3) in the vacuole. We determined, therefore, that delivery of the two respective nuclear reporters to the vacuole is temporally and spatially separated. Furthermore, our data suggest that LN is mechanistically distinct from PMN because it can occur in nvj1Δ and vac8Δ cells, and does not require ATG11. Nevertheless, a subset of the components of the core macroautophagic machinery is required for LN as it is efficiently inhibited in null mutants of several autophagy-related genes (ATG) specifying such components. Moreover, the inhibition of LN in some mutants is accompanied by alterations in nuclear morphology.